The g-good-neighbour conditional diagnosability of multiprocessor system based on half hypercube. Issue 3 (3rd July 2018) - Lv, Mengjie; Zhou, Shuming; Sun, Xueli; Lian, Guanqin; Chen, Gaolin
ABSTRACT: Fault diagnostic analysis is an important evaluation in the design and maintenance of multiprocessor systems. The g -good-neighbour conditional diagnosability is the maximum number of faulty vertices a multiprocessor system can guarantee to identify under the condition that every fault-free vertex has at least g fault-free neighbours. In this paper, we first establish the -connectivity of multiprocessor system based on half hypercube and then show that the g -good-neighbour conditional diagnosabilities of half hypercube under the PMC model and MM* model are for and . As a by-product, we also derive the g -good-neighbour conditional diagnosability of hierarchical cubic network since an n -dimensional half hypercube network is isomorphic to an n /2-dimensional hierarchical cubic network when n is even.